Structure of the germline genome of Tetrahymena thermophila and relationship to the massively rearranged somatic genome - Hamilton, Eileen P; Kapusta, Aurélie; Huvos, Piroska E; Bidwell, Shelby L; Zafar, Nikhat; Tang, Haibao; Hadjithomas, Michalis; Krishnakumar, Vivek; Badger, Jonathan H; Caler, Elisabet V; Russ, Carsten; Zeng, Qiandong; et al. (eLife, 2016)
The germline genome of the binucleated ciliate Tetrahymena thermophila undergoes programmed chromosome breakage and massive DNA elimination to generate the somatic genome. Here, we present a complete sequence assembly of the germline genome and analyze multiple features of its structure and its relationship to the somatic genome, shedding light on the mechanisms of genome rearrangement as well as the evolutionary history of this remarkable germline/soma differentiation. Our results strengthen the notion that a complex, dynamic, and ongoing interplay between mobile DNA elements and the host genome have shaped Tetrahymena chromosome structure, locally and globally. Non-standard outcomes of rearrangement events, including the generation of short-lived somatic chromosomes and excision of DNA interrupting protein-coding regions, may represent novel forms of developmental gene regulation. We also compare Tetrahymena’s germline/soma differentiation to that of other characterized ciliates, illustrating the wide diversity of adaptations that have occurred within this phylum.
Keywords: Tetrahymena thermophila; chromosome breakage; intermal eliminated sequence; genome rearrangement; transposable element; centromere